Universal scaling laws of collective human flow patterns in urban regions - Yohei Shida (Nature Portfolio, 2020)
Abstract Detail observation of human locations became available recently by the development of information technology such as mobile phones with GPS (Global Positioning System). We analyzed temporal changes of global human flow patterns in urban regions based on mobile phones’ GPS data in 9 large cities in Japan. By applying a new concept of drainage basins in analogous to river flow patterns, we discovered several universal scaling relations. These include, the number of moving people in a drainage basin of diameter L is proportional to $$L^3$$ L 3 in the morning rush hour, which is surprisingly different from reasonable intuition of proportionality to the 2 dimensional area, $$L^2$$ L 2 . We show that this unexpected 3 dimensional feature is related to the strong attraction of the city center to become a 3 dimensional structure due skyscrapers.